Effect of bimodal silica-alumina-supported metallocene catalyst for ethylene/α-olefin copolymerization - Pongsathorn Wongwaiwattanakul (Chulalongkorn University, 2014)
Thesis (M.Eng.)--Chulalongkorn University, 2007